1999
DOI: 10.1055/s-2007-978731
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Homeostasis During Oral Glucose Load in Healthy Women

Abstract: It has been demonstrated that in healthy subjects during oral glucose tolerance test, serum calcium declines, while urinary calcium excretion increases, even if there is not a general agreement in this regard. The study was carried out in order to evaluate the effects of glucose oral load on calcium homeostasis in eight healthy adult women, also considering ionized calcium, plasma insulin and parathyroid hormone changes. The results showed a decline of total and ionized serum calcium (p < 0.05 and p < 0.01, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 15 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…In humans, it was reported that hyperglycemia induced by oral glucose load caused a slight decrease in serum calcium (1.28 to 1.27 mmol/L) and an increase in urinary calcium discharge. Those were in parallel with a decrease in parathyroid hormone level (D'Erasmo et al , 1999). However, the hypocalcemia we observed is much more severe than that described in an earlier report, and the reasons remain elucidated.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In humans, it was reported that hyperglycemia induced by oral glucose load caused a slight decrease in serum calcium (1.28 to 1.27 mmol/L) and an increase in urinary calcium discharge. Those were in parallel with a decrease in parathyroid hormone level (D'Erasmo et al , 1999). However, the hypocalcemia we observed is much more severe than that described in an earlier report, and the reasons remain elucidated.…”
Section: Discussionmentioning
confidence: 92%
“…As an interesting novel finding, we found that a sustained hypocalcemia accompanies hyperglycemia and acidosis after AMP treatment, and the hypocalcemia may therefore be the reason for the increased seizure rate after stroke. The mechanisms for the hypocalcemia are not clear, although parathyroid hormone suppression is suggested (D'Erasmo et al , 1999). In humans, it was reported that hyperglycemia induced by oral glucose load caused a slight decrease in serum calcium (1.28 to 1.27 mmol/L) and an increase in urinary calcium discharge.…”
Section: Discussionmentioning
confidence: 99%
“…In eight healthy subjects, rifampicin treatment reduced circulating levels of 25-hydroxyvitamin D and 1␣,25-(OH) 2 D 3 by 34 and 23%, respectively. In addition, rifampicin and phenobarbital are two of the drugs most frequently associated with osteomalacia, a metabolic bone disease characterized by a defect of bone mineralization frequently due to an alteration of vitamin D metabolism (53). This suggests that CAR and/or PXR might be involved in the control of genes involved in vitamin D synthesis or catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Our own unpublished data showed that this is partially a result of decreases in serum albumin, presumably representing hemodilution related to the osmotic changes that accompany the absorption of a glucose load. However, ionized calcium also decreases, and there is an increase in urinary calcium excretion (60) . These changes are likely to be contributed to by reduced PTH secretion, (60,61) increased circulating concentrations of amylin (which has a calciuric action through the renal calcitonin receptor (62,63) ), and increased calcitonin secretion (64) .…”
Section: Peptides Responsive To Feedingmentioning
confidence: 99%
“…However, ionized calcium also decreases, and there is an increase in urinary calcium excretion (60) . These changes are likely to be contributed to by reduced PTH secretion, (60,61) increased circulating concentrations of amylin (which has a calciuric action through the renal calcitonin receptor (62,63) ), and increased calcitonin secretion (64) . There is also evidence of reduced bone resorption after feeding of fat, protein, or glucose in humans (65–67) .…”
Section: Peptides Responsive To Feedingmentioning
confidence: 99%